Implementation of Path Analysis for Modeling the Influence of Organizational Culture on Work Productivity - Abdussamad, Siti Nurmardia; Abdussamad, Zuchri; Reza, Widya; Aqmal, Ikhlas Ul (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This research aims to determine the significant factors of organizational culture that influence employee performance productivity using a path analysis model by looking at the total direct and indirect influence of sub-variables. Path analysis can describe the magnitude of the influence and significant variables using direct and indirect influences. By adapting to this case, direct and indirect modeling is needed to see the magnitude of the influence of these sub-indicators. Research related to organizational culture has been carried out to see how much influence organizational culture and motivation have on employee performance. The result is that the greater the organizational culture and achievement motivation, the higher the influence on employee performance. This type of research uses a qualitative and quantitative approach. This research uses a questionnaire to collect data, which has been tested for validity and reliability. This research was conducted at the Gorontalo District Health Service in 2022. Respondents used in this research were 57 Gorontalo District Health Service employees. Data analysis using software R. Results of the research show that organizational culture variables and sub-variables, namely artifacts (X1), values ​​(X2), and basic assumptions (X3), significantly influence employee performance productivity (Y). The total effect is calculated using the path coefficient calculation of the significant variables. The total influence of organizational culture in the form of artifacts (X1) on employee work productivity (Y) is 72%, and the total influence of organizational culture in the form of values ​​(X2) on employee work productivity (Y) is 65%. The total influence of organizational culture is in the form of basic assumptions (X3 ) on employee work productivity (Y) of 78%. This shows that the organizational culture variable influences the most significant influence, namely basic assumptions (X3). The Gorontalo district health office can consider the results of this analysis to make further policies regarding which organizational culture priorities will be implemented to increase employee productivity to the maximum.